Training and Racing Behavior of Recreational Runners by Race Distance—Results From the NURMI Study (Step 1) - Knechtle, Beat; Tanous, Derrick R.; Wirnitzer, Gerold; Leitzmann, Claus; Rosemann, Thomas; Scheer, Volker; Wirnitzer, Katharina (Frontiers in Physiology, 2021)
The present study investigated pre-race preparation of a large sample of recreational runners competing in different race distances (e.g., shorter than half-marathon, half-marathon, marathon and ultra-marathon). An online questionnaire was used and a total of 3,835 participants completed the survey. Of those participants, 2,864 (75 %) met the inclusion criteria and 1,628 (57 %) women and 1,236 (43 %) men remained after data clearance. Participants were categorized according to race distance in half-marathon (HM), and marathon/ultra-marathon (M/UM). Marathon and ultra-marathon data were pooled since the marathon distance is included in an ultra-marathon. The most important findings were (i) marathon and ultra-marathon runners were more likely to seek advice from a professional trainer, and (ii) spring was most commonly reported across all subgroups as the planned season for racing, (iii) training volume increased with increasing race distance, and (iv) male runners invested more time in training compared to female runners. In summary, runners competing in different race distances prepare differently for their planned race.